EXPERIMENTAL INVESTIGATION OF THE INFLUENCE OF FEEDSTOCK MOISTURE CONTENT ON THE YIELD AND QUALITY OF THE PRODUCT FROM THE THERMO-CATALYTIC REFORMING PROCESS - Onyishi, Hillary Onyebuchi; Daschner, Robert; Neidel, Johannes; Franke, Matthias; Apfelbacher, Andreas; Hornung, Andreas (European Biomass Conference and Exhibition Proceedings, 2022)
The use of auger reactors in thermo-catalytic reforming (TCR®) plants demand the feedstocks to be granulated or pelletised and dried. Drying improves the compressive strength and shelf life of the granules or pellets. This work investigates the optimal moisture content for feedstocks intended for the lab-scale TCR® plant. Four pelletised samples from woody biomass with moisture contents 0.23 wt.%, 1.09 wt.%, 10.65 wt.% and 30.79 wt.% are studied. The experimental settings are kept the same for all the samples. The results show that, generally, the dryer the feedstock, the bigger the bio-oil and bio-gas yields. However, excessive drying does not bring about commensurate increase in the bio-gas and bio-oil yields. More still, the moderately dry (10.56 wt. %) sample presents the least difficulty in material handling while having optimal yields. Meantime, it is observed from the proximate and ultimate analyses of the products that the moisture content of the feed does not have any significant influence on the properties of the products. Based on these results, the optimal moisture content recommended for feedstocks intended for the lab-scale TCR® plant is approximately 10 wt.%.
CRIS-Team Scopus Importer:2022-12-02
Keywords: auger reactors; biomass; moisture content; thermo-catalytic reforming

THERMO-CATALYTIC REFORMING OF GENERAL WASTE TO PRODUCE BIOFUELS - Onyishi, Hillary Onyebuchi; Neidel, Johannes; Daschner, Robert; Franke, Matthias; Apfelbacher, Andreas; Hornung, Andreas (European Biomass Conference and Exhibition Proceedings, 2022)
This work investigates the feasibility of extracting biofuels from general waste through the novel thermo-catalytic reforming (TCR®) technology. Two feedstocks (Up-Sieve Material and Grey Compost) supplied from Risorse Ambiente Palermo (RAP) are studied. They are shredded, pelletised and characterised. The proximate analyses show the Up-Sieve feed has a higher heating value (HHV) of 17.6 MJ/kg with an ash content of 19.60 wt.%, while the Grey Compost feed has a HHV of 11.5 MJ/kg and an ash content of 40.16 wt.%. The results of the TCR® experiments on both feeds show that the Up-Sieve feed has more gas and oil yields while the Grey Compost has more char yield. The results from the characterisation of the oils and chars from both feeds show the oils have HHVs of 38.2 MJ/kg and 37.0 MJ/kg while the chars have HHVs of 13.6 MJ/kg and 5.7 MJ/kg respectively. Except for the char from the Grey Compost (with the 5.7 MJ/kg HHV), the products can be applied directly as biofuels due to their sufficient calorific values. By and large, the successful extraction of biofuels from general waste is a huge step in waste management and environmental protection.
CRIS-Team Scopus Importer:2022-12-02
Keywords: biofuels; thermo-catalytic reforming; thermochemical conversion; waste